T4 dependence of the nuclear quadrupole resonance frequencies in solids. II - Schempp, Ellory; Silva, P. R.P. (AIP Publishing, 1973)
Analyses of experimental data for NQR frequency shifts as a function of temperature reveal a dominant T4 dependence at sufficiently low temperature, T ≲ 20°K, in accord with a recent prediction. The results indicate the necessity of adding a Debye term to the usual Bayer expression. The coefficient of the Debye term is shown to vary with TD-5; preliminary results indicate that values of the Debye temperature TD may be obtained from low temperature NQR data.